A Comprehensive Analysis of Legal Frameworks and Ethical Considerations in Outer Space Exploration and Utilization - Mohamed Babiker Mohamed Malik (المجلة الدولية للبحوث والدراسات القانونية, 2026)
The continuing expansion of space, regarded as a shared human heritage, is encountering an increasing number of obstacles due to the swift progression of technology. The proliferation of satellites and space debris poses a threat to the delicate biosphere in outer space as well as on Earth. Thus, attorneys labored over "Space Law" to regulate worldwide planetary exploration, research missions, and astronaut safety. This study traces the dual-track evolution of space law over the years as it investigates its ever-changing landscape. The inaugural segment of this study examines international law, including that which has been established through bilateral agreements with organizations like the Arab Satellite Communications Organizations and the United Nations. Furthermore, this study explores the potential for various national legal systems to regulate space operations in a manner that protects the rights of stakeholders, guarantees adherence to international standards, and complies with global norms. The research technique examines all relevant domestic and international space exploration rules. This article examines the historical influence of key international organizations on space law and bilateral agreements. These organizations include IISL, COPUOS, ITU, and WMO. The research indicates that national and international policies exert an influence on space laws. Collaboration among numerous entities, including governments, is vital for the ethical and sustainable conduct of space exploration. The development of space law has brought to the forefront the significance of international cooperation and legislation by states that adhere to global standards. Space legislation must be codified in order to safeguard ecosystems and human lives.